(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article deals with various methods of activating the cognitive activity of students. The use of interactive technologies is demonstrated in foreign language classes. The article shows the stimulation of cognitive interest of students using various forms of individual work. The levels of development of students’ cognitive activity are determined, which makes it possible to diagnose and manage the activities of students focused on the educational process. To achieve this goal, various traditional pedagogical technologies are used, adapted, and innovative teaching methods are created. The performed analysis suggests how the teacher achieves his goal with the help of modern developing pedagogical technologies and active teaching methods. A future specialist needs training in the practical acquisition of a foreign language. The article considers the conditions that help to develop the thinking system in a foreign language as one of the methods of increasing cognitive activity, and the methodological aspects of successful discussion. Ways to encourage students to express their thoughts in a foreign language are considered. As a result of the use of interactive technologies, students’ interest and motivation in learning increases.